Polyacrylamide Functionalized Graphene Oxide/Alginate Beads for Removing Ciprofloxacin Antibiotics - Jung-Weon Choi; Sang-June Choi (Toxics, 2022)
Ciprofloxacin (CPX), a widely used antibiotic, was removed by synthesizing graphene oxide/calcium alginate–polyacrylamide (GO/Ca-Alg2–PAM) beads, a three-dimensional double-network complex. The synthesis of GO/Ca-Alg2–PAM beads was performed by crosslinking and cation exchange mechanisms with graphene oxide (GO), sodium alginate (Na-Alg), and polyacrylamide (PAM). The properties of GO/Ca-Alg2–PAM beads were confirmed using field emission scanning electron microscopy, Fourier transform infrared spectroscopy, and a thermogravimetric analysis. Furthermore, isothermal adsorption experiments were performed and fitted using three isothermal adsorption models (Langmuir, Freundlich, and Temkin). The adsorption isotherm experimental data fit well with the Langmuir isotherm model with a qm value of 6.846 mg/g. In addition, the spontaneous reaction of the CPX adsorption using GO/Ca-Alg2–PAM was confirmed by temperature-dependent experiments.